2018
DOI: 10.1177/1475921718792108
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility use of in-line Mach–Zehnder interferometer optical fibre sensor in lightweight foamed concrete structural beam on curvature sensing and crack monitoring

Abstract: This article presents a novel study on curvature sensing and crack monitoring in lightweight foamed concrete structural beam using the packaged fibre-based in-line Mach–Zehnder interferometer curvature sensor. The Mach–Zehnder interferometer sensors which consist of two abrupt biconic tapers were fabricated and packaged into polypropylene slabs to protect the sensors under harsh condition of the real sensing environment, as the sensors were embedded into lightweight foamed concrete structural beams for field t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…We should highlight that the sensor 5 (based on ARROW effect) has a high sensitivity, but only measures large curvatures within a narrow curvature range. Based on these parameters, this sensor will not exhibit good performance for structural health monitoring applications where low curvatures are measured [30]. The sensor 3 shows a similar curvature range, but it requires further processing for the taper and has a lower sensitivity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We should highlight that the sensor 5 (based on ARROW effect) has a high sensitivity, but only measures large curvatures within a narrow curvature range. Based on these parameters, this sensor will not exhibit good performance for structural health monitoring applications where low curvatures are measured [30]. The sensor 3 shows a similar curvature range, but it requires further processing for the taper and has a lower sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…It must be pointed out that the thickness of the polymer layer was 2 mm, and the sensor was set in the middle of this polymer layer (this position inside the material is called the neutral axis). This axis does not suffer any elongation when the segment is bent [30]. We decided to put the sensor in this position to guaranty that it does experience any strain due to the polymer.…”
Section: Fabrication Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the development of various types of contact sensors, some contact sensor-based crack detection methods have been studied (Narayanan et al, 2018;Yan et al, 2019). Leung et al (2000) and Png et al (2018) developed a new fiber optic sensor for cracks detection. Experimental results showed that the sensor can detect tiny cracks of about 0.1 mm.…”
Section: Introductionmentioning
confidence: 99%
“…1 Early detection of undersized damage in the scale of several millimeters has been facilitated by numerous damage detection methods developed in recent decades, typified as eddy current nondestructive testing, laser interferometry measurement, and ultrasonics-based structural health monitoring (SHM), to name a few. [2][3][4][5][6] Among these approaches, ultrasonics-based SHM has been widely utilized to implement real-time monitoring of the operation and health status of engineering assets, using various piezoelectric sensors such as piezoelectric lead zirconate titanate (PZT) and transducers that can be utilized to perceive guided ultrasonic waves (GUWs). However, certain drawbacks of these piezoelectric sensors have limited the further development of SHM.…”
Section: Introductionmentioning
confidence: 99%